Optimalisasi Akun Media Sosial Instagram Pada Zerone Outdoor Ciamis - Ernawati; Fauji, Salman (EKOBIMA, 2023)
For Zerone Outdoor, Instagram is the main bridge to promote their products to the general public in an easy and cost-effective way. They have been trying to market their services through Instagram and have been active since they started their rental business, but they have not been able to maximize their sales using the Instagram social media platform.The purpose of this research is to understand how Zerone Outdoor utilizes Instagram as a digital marketing tool. The research conducted is qualitative and descriptive in nature, and the data collection methods employed by the researcher include interviews and documentation to explore the issues more openly and obtain reliable data. Based on the research findings, it can be concluded that the optimization of Zerone Outdoor Instagram account in utilizing and implementing SMO (Social Media Optimization) on their social media platform has been successful or in accordance with the theories explained